Right ventricular infarction complicated by right to left shunting through an atrial septal defect: successful treatment with an Amplatzer septal occluder. Issue 4 (16th March 2005) - Bassi, S; Amersey, R; Andrews, R
Abstract : A 68 year old woman presented with right ventricular myocardial infarction complicated by refractory hypoxaemia. She was found to have a significant right to left shunt at the atrial level through a previously undiagnosed ostium secundum atrial septal defect. Percutaneous closure of the atrial septal defect with an Amplatzer septal occluder resulted in prompt improvement in her oxygenation and clinical state. Such closure should be considered for patients with right ventricular infarction and refractory hypoxaemia caused by a right to left interatrial shunt.